Emulsifying Properties of Proteins Extracted from Jatropha curcas L. to Harvest Chlorella vulgaris sp. Microalgae - Khodapanah, Nasrin; N., Syairah; Mohd Mustaqim, .; Syed Mahmood, . (EM International., 2023)
A bio-floatation technique was used to test the effectiveness of Jatropha curcas seed extract in recoveringmicroalgae from an aqueous medium. This technique used Jatropha curcas oil-protein extract emulsion forfloatation removal of Chlorella vulgaris microalgae. The effects of variables have been investigated in thisprocess, including operating parameters such as protein-oil emulsion dosage, pH, and mixing time. Amaximum floatation efficiency of 81% was observed when a 20 ml/l protein-oil emulsion dosage wastested at pH 2 and a mixing time of 4 min. Furthermore, the analysis of the microalgaeâs zeta potentialchanges revealed a notable variation in value caused by the protein-oil emulsion. This bio-floatation techniqueis useful for the high-efficiency harvesting of microalgae to produce cost-effective biofuel.